EU-jäsenyyden vaikutus lihasikatilojen talouteen - Lempiö, Pasi (Maatalouden taloudellinen tutkimuslaitos, 1996)
The objective of this study is to determine how the change in agricultural policy and market conditions changes the economy of Finnish fattening pig farms. The economy of these farms is evaluated with the measures of liquidity, profitability, and solvency. Based on the data of 32 book-keeping farms in 1993, a static simulation model, i.e. the physical production processes are assumed to remain constant, is used to project the economic situation of these farms for 1995 - 2000. The same data is used in the support areas A (southern coast), B (southern Finland) and C1 (central Finland). Projected input and output prices, and support forms relevant to the particular farms are taken into account in the model. The farms were divided into three groups with respect to their cost-efficiency in 1993. The impacts of EU membership for the farms of different cost-efficiency levels are examined. For example, the decrease of net farm income from 1993 to 1995 is considerable in every examined area. In addition, in the areas A and B, the net farm income will decline rapidly during the transitional period (1995 - 1999) as the transitional period support decreases. At the same time, the net farm income in the area C1 will remain fairly constant because of the Nordic support. The absolute differences between the groups will decrease according to all measures used, but the differences will remain yet considerable in the most measures. While evaluating the results, one must consider the nature of the static model used, and that the farms used as data are larger and more efficiently operated than the average fattening pig farms in Finland.
Keywords: Ma; EU; Suomi; sikatilat; maksuvalmius; kannattavuus; Euroopan unioni; pig farms; profitability; European Union; solvency; Finland